Development of G-quadruplex ligands for selective induction of a parallel-type topology. Issue 40 (6th September 2018) - Ma, Yue; Tsushima, Yamato; Sakuma, Mai; Sasaki, Shogo; Iida, Keisuke; Okabe, Sachiko; Seimiya, Hiroyuki; Hirokawa, Takatsugu; Nagasawa, Kazuo
Abstract : Parallel type of topology in G4 is selectively induced by tetra-guanidinylalkyl substituted 6OTD derivative. Abstract : G-Quadruplex structures (G4s) in guanine-rich regions of DNA play critical roles in various biological phenomena, including replication, translation, and gene expression. The G4-forming DNAs can form three kinds of topologies, i.e., parallel, anti-parallel, and hybrid. In this paper, we present G4 ligands L2H2-2M2EA-6OTD (3 ) and L2G2-2M2EG-6OTD (4 ) bearing tetra-aminoalkyl and -guanidinylalkyl side chains, respectively, in a macrocyclic hexaoxazole structure. These ligands efficiently induce the parallel-type topology of telomeric G4 regardless of the effects of cations. Titration with4 results in a drastic topology switch to the parallel topology from the anti-parallel structure induced by the structurally related ligand L2H2-6OTD (1 ).